Ultra-stable antibody fragments with a novel disulfide bridge stabilized framework – construction of a disulfide bridge stabilized antibody library - Haapalinna, Anna (My University, 2022)
The single-chain fragment variable (scFv) is the smallest antibody fragment that can bind antigen. The scFvs have many advantages over the full-length antibodies and are therefore used in many biotechnical and medicinal applications. However, many scFvs are prone to aggregation and oligomerization and possess lower thermostability than the corresponding antibodies. In this study, an scFv derived from anti-human epidermal growth factor 2 (HER2) trastuzumab was stabilized by introducing a disulfide bridge in a novel position between two complementary determining regions (CDR-H3 and CDR-L1). The introduction of the interloop disulfide bridge in the position 100B and L34 (Kabat) increased the thermostability of the soluble proteins and scFvs displayed on phages while retaining their antigen-binding properties. The novel disulfide stabilized scFv (ds-scFv) framework was exploited in constructing a CDR-H3 library. Enrichment of phages specific to HER2 was observed in phage display selection trials, and sequencing of single clones from enriched libraries identified several unique clones. The promising results encourage further characterization of the novel ds-scFv constructs for possible medicinal applications targeting HER2. In addition, the novel framework can be used to construct a more diverse universal stabilized antibody library that can be used as a source of bioreagents for various antigens.